Good Transport Practices in University of West Attica - P. Papantoniou; P. Kaldis (Journal of Sustainability Perspectives, 2022)
University of West Attica operates in three Campuses, all within the metropolitan region of Attica, indicating that the mobility characteristics of these campuses are similar to urban models and in most cases, could be used as a test area for mobility policies related to public transport, multimodality or transport restrictions. Within the Cοvid-19 period, University of West Attica made important progress in transport related issues that are very critical for the smooth operation of the campuses and the University as a whole. The key transport related good practices refer to several thematic areas including parking management, soft modes infrastructure, public transport, car related issues, road infrastructure, environment, and energy. All these key interventions have a positive impact not only for the members of the academic society of University of West Attica but also to the mobility characteristics of West and Central Attica where university campuses are located and interact with Attica residents and tourists.Keyword: University of West Attica, Campus, Urban Mobility, Transport, Parking